The prevalence of the ABCB1-1Δ variant in a clinical veterinary setting: The risk of not genotyping - Evy Beckers; Iris Casselman; Emma Soudant; Sylvie Daminet; Dominique Paepe; Luc Peelman; Bart J. G. Broeckx (PLoS ONE, 2022)
Multidrug sensitivity is an autosomal recessive disorder in dogs caused by a 4-bp deletion in the ABCB1 gene, often referred to as the ABCB1-1Δ variant. This disease has a high prevalence in some breeds and causes adverse reactions to certain drugs when given in normal doses. Though most dogs known to be at risk are of the collie lineage or were traced back to it, the variant has also been described in several seemingly unrelated breeds. It is generally advised to genotype dogs at risk before treating them. However, there seems to be a discrepancy between the advice and current veterinary practices, as a recent study in Belgium and the Netherlands showed that most veterinarians never order a DNA test. To assess the possible risk of not testing for multidrug sensitivity in a clinical setting, the ABCB1-1Δ variant allele frequency was established in a sample of 286 dogs from a veterinary clinic. This frequency was compared to the allelic frequency in 599 samples specifically sent for genetic testing. While the allelic frequency in the sample for genetic testing was high (21.6%) and in line with the general reports, the allelic frequency in the clinical setting was low (0.2%), demonstrating an enormous difference between laboratory and clinical frequencies. Because of the low frequency of the disease-causing variant in the general clinical population, the risk of encountering a dog displaying multidrug sensitivity despite not genotyping seems to be low. As the variant was only found in an at-risk breed, the current recommendation of routinely genotyping at-risk breeds before treatment seems justified.